EXPERIMENTAL STUDY OF FORCED CONVECTION ENHANCEMENT IN A POROUS AIR DUCT: EFFECTS OF POROSITY AND PARTICLE SIZE - Hameed, Mohammed Z.; Weis, Musa Mustafa (Antis-Publisher, 2026)
Objective: This research focuses on experimental studies of forced convection heat transfer in an air duct packed with a glass ball porous medium to enhance thermal efficiency and save energy. Method: Experiments were conducted with heat inputs of 100, 150, and 200 W and air velocities of 0.5, 0.75, and 1 m/s, while varying the ball diameter and porosity. Three electric tubular heaters fixed vertically were used for uniform heating. Results: The study shows that lower porosity media significantly increase heat transfer capability under the same airflow conditions. Glass balls with a porosity of 0.58 achieved a maximum enhancement, with increments of 66.10%, 89.79%, and 64.83% at 0.5 m/s for 100, 150, and 200 W, respectively. A strong linear relationship between Reynolds and Nusselt numbers was observed, with maximum Nusselt number enhancements of 72.92% and 24.61% at 0.5 and 0.75 m/s, respectively. Novelty: This study highlights the impact of glass ball size and porosity on heat transfer performance, demonstrating that smaller particles with higher porosity significantly improve thermal efficiency, though at the cost of increased flow resistance. The findings contribute valuable insights into optimizing porous media for energy-efficient heat transfer.